PENGEMBANGAN BUKU AJAR NORMA DAN PENERAPANNYA BERBASIS KEARIFAN LOKAL SEMARANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V - Arifa, Dwi; Sari, Nawang Wulan; Widodo, Susilo Tri; Aniswatin, Nor (Universitas Negeri Semarang, 2023)
Textbooks are one of the learning resources needed in the learning process. The aim of this research is to develop a textbook on Norms and their Application based on the local wisdom of Semarang City. The research method used is Research and Development. The development model used is the ADDIE model which starts from analysis, design, development, implementation and evaluation. The subjects in this research were fifth grade students at SD Negeri Wates 02. The data collection techniques used were interviews, observations and tests. To determine the suitability of a textbook, it must be assessed by media experts and material experts. The validation test results show that the textbook developed is in the very appropriate category both in terms of media and material. The percentage of media validation test results is 93% while the material validation test results are 91,66%. Meanwhile, the effectiveness of textbooks is carried out through tests. As many as 92% of students have completed and only 8% have not completed. From the results of validation tests and tests, this textbook can be said to be feasible and effective.